Formal techniques for safety-critical systems : fourth International Workshop, FTSCS 2015, Paris, France, November 6-7, 2015. Revised selected papers /: fourth International Workshop, FTSCS 2015, Paris, France, November 6-7, 2015. Revised selected papers. (2016) - Unknown
No abstract available